2018
DOI: 10.1097/jcn.0000000000000511
|View full text |Cite
|
Sign up to set email alerts
|

Health Beliefs and Medication Adherence in Omanis With Hypertension

Abstract: Patients' beliefs are important consideration to improve medication adherence. Clinically, patients' beliefs should be assessed, and strategies to improve medication adherence should incorporate beliefs as a key component to improve antihypertensive medication adherence. Patient education and counseling regarding hypertension and necessity and side effects of medications are important to maximize positive beliefs and improve medication adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
38
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 57 publications
10
38
1
3
Order By: Relevance
“…In our study, the dimensions of attitude and behavior in medication literacy as well as annual incomes for hypertensive patients were found to be independent predictors associated with medication adherence. A range of studies have examined patients’ attitudes toward hypertension and their medication treatment or health beliefs about hypertension in relation to adherence, and the results were consistent with our study (Boima et al, 2015; Kang et al, 2015; Al-Noumani et al, 2018). Fewer concerns about medication (Boima et al, 2015), stronger and positive beliefs about hypertension, self-perceived disease severity, and medication necessity (Lo et al, 2016; Jande et al, 2017; Al-Noumani et al, 2018), as well as good self-perceived health status (Kang et al, 2015) were found to be associated with higher adherence.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In our study, the dimensions of attitude and behavior in medication literacy as well as annual incomes for hypertensive patients were found to be independent predictors associated with medication adherence. A range of studies have examined patients’ attitudes toward hypertension and their medication treatment or health beliefs about hypertension in relation to adherence, and the results were consistent with our study (Boima et al, 2015; Kang et al, 2015; Al-Noumani et al, 2018). Fewer concerns about medication (Boima et al, 2015), stronger and positive beliefs about hypertension, self-perceived disease severity, and medication necessity (Lo et al, 2016; Jande et al, 2017; Al-Noumani et al, 2018), as well as good self-perceived health status (Kang et al, 2015) were found to be associated with higher adherence.…”
Section: Discussionsupporting
confidence: 90%
“…For patients with hypertension, lifetime and persistent antihypertensive therapy is one of the most effective ways to achieve ideal blood pressure levels (Sabaté, 2003). In addition, it has been confirmed that suboptimal blood pressure control is closely associated with patients’ poor adherence or nonadherence to antihypertensive drugs (Morisky et al, 2008; Abegaz et al, 2017; Al-Noumani et al, 2018; Beune et al, 2019; Uchmanowicz et al, 2019). Patients with poor adherence were found to be at 1.417 times more likely to have uncontrolled hypertension than those with good adherence (Xue et al, 2019).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…In Pouliot's study, patient's beliefs and personal circumstances were considered into the medication literacy conceptualization, it was a two-way dialogue between patients and their healthcare providers about the benefits, risks, and alternatives of treatment, in order to achieve optimal goal and outcomes of individual's medication literacy (Pouliot et al, 2018). Specifically, for hypertensive patients, their beliefs and attitudes to the severity of hypertension disease, to the necessity of antihypertensive taking and of the treatment plan discussion with healthcare providers, as well as their self-efficacy were playing a critical role in their adherence to antihypertensive drug taking and self-management (Al-Noumani et al, 2018;Al-Noumani et al, 2019;Qvarnström et al, 2019). Therefore, hypertensive patients' attitudes, including their beliefs related to hypertension severity and susceptibility, their beliefs to the effectiveness or necessity of taking antihypertensive medication, as well as their self-efficacy in hypertension disease management, were incorporated into the conceptualization and operationalization of hypertensive patients' medication literacy.…”
Section: Introductionmentioning
confidence: 99%